Identity and the Ethics of Tolerance - Geels, Antoon (Tattva Journal of Philosophy, 2021)
Our self-image is constructed in the interplay between man and culture. Religious traditions play a key role in this interplay; myths create meaning to the individual and to society at large. Sacred narratives provide man with patterns of behavior, how life should be lived. The other side of the picture is that identity and integrity may lead to intolerance, a dividing line between them and us: the most serious obstacle to peace and intercultural understanding. Religions can reinforce strong feelings of humiliation, of being a victim. This, in turn, may lead to the splitting of humanity into good and evil; one group demonizes the other. This coupled with an idealized, wrathful and punitive deity or leader may lead to violence, and violence is sanctified. Religion may encourage feelings of humiliation, but it can also deliver an antidote. There are theological resources that can counter terror and violence. A merciful and compassionate God can replace a wrathful and punitive deity. A stage of faith known as gerotranscendence is characterised by “an increasing feeling of belonging to the universe”. Representatives of ‘glocal’ spirituality reject claims of exclusivity. A glocal perspective is crucial. What we need today is that a greater number of spiritual leaders stand up and insist on values that touch upon the sanctity of life.